Correlation of Immune Markers With Outcomes in Biliary Atresia Following Intravenous Immunoglobulin Therapy. Issue 5 (25th March 2019) - Kim, Sehee; Moore, Jeffrey; Alonso, Estella; Bednarek, Joseph; Bezerra, Jorge A.; Goodhue, Catherine; Karpen, Saul J.; Loomes, Kathleen M.; Magee, John C.; Ng, Vicky L.; Sherker, Averell H.; Smith, Caroline; et al.
Abstract : Biliary atresia is a progressive fibroinflammatory cholangiopathy of infancy that is associated with activation of innate and adaptive immune responses targeting bile ducts. A recently completed multicenter phase I/IIA trial of intravenous immunoglobulin in biliary atresia did not improve serum total bilirubin levels at 90 days after hepatoportoenterostomy or survival with the native liver at 1 year. A mechanistic aim of this trial was to determine if the peripheral blood immunophenotype was associated with clinical outcomes. Flow cytometry of peripheral blood cell markers (natural killer [NK], macrophage subsets, T‐ and B‐cell subsets, regulatory T cells), neutrophils, and activation markers (clusters of differentiation [CD]38, CD69, CD86, human leukocyte antigen‐DR isotype [HLA‐DR]) was performed on 29 patients with biliary atresia at baseline and at 60, 90, 180, and 360 days after hepatoportoenterostomy. Plasma cytokines and neutrophil products were also measured. Spearman correlations of change of an immune marker from baseline to day 90 with change in serum bilirubin revealed that an increase in total bilirubin correlated with 1) increased percentage of HLA‐DR + CD38 + NK cells and expression of NK cell activation markers CD69 and HLA‐DR, 2) decreased percentage of regulatory T cells, and 3) increased interleukin (IL)‐8 and associated neutrophil products (elastase and neutrophil extracellular traps). Cox modeling revealed that the change from baseline to day 60 of the percentage of HLA‐DR + CD38 + NK cells and plasma IL‐8 levels was associated with an increased risk of transplant or death by day 360. Conclusion: Poor outcomes in biliary atresia correlated with higher peripheral blood NK cells and IL‐8 and lower regulatory T cells. Future studies should include immunotherapies targeting these pathways in order to protect the biliary tree from ongoing damage. Abstract : The aim of this study was to determine if the peripheral blood immunophenotype in biliary atresia was associated with clinical outcomes. An increase in total bilirubin post‐Kasai (poor outcome) correlated with increased HLA‐DR+CD38+ natural killer cells, decreased regulatory T cells and increased IL‐8 and associated neutrophil products. Future studies should include immunotherapies targeting these pathways in order to protect the biliary tree from ongoing damage.